Journal In-House Style Based on Mendeley's Metadata Extraction - Dhevi Enlivena Irene Restia Mahelingga (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
A reference manager such as Mendeley Desktop is needed to make it easier for scientific paper writers to automatically generate bibliography. However, metadata of several refereed journal articles cannot be extracted properly by Mendeley. Errors in generating a journal’s metadata will certainly disadvantage the authors of the cited article and journal. Mistakes in citation can also threaten the citer with plagiarism. This study seeks to find an in-house style that can be accurately detected by Mendeley Desktop as a reference for journal managers to make their journals’ metadata can be properly extracted. The study investigates samples of 27 articles from 27 different journals published by LIPI. The accuracy of metadata extraction of the sample articles is examined on Mendeley Desktop version 1.19.4 and refers to Mendeley’s metadata extraction pipeline with eight assessment variables. The accuracy percentage from Mendeley Desktop's metadata extraction is analyzed using a descriptive approach. It was found that variable of journal titles in all journals can not be extracted which gives the maximum accuracy percentage of 87.5%, with only four journals that get this percentage. There are nine indicators that can be followed to achieve this percentage. For journal managers, setting the layout of journal articles based on Mendeley Desktop’s or Google Scholar’s convention in extracting metadata needs to be considered in the digital era. However, advances in information technology have an influence on the visual layout and the in-house style of scientific papers.